Program Prioritas BSPS Dalam Pengaruhnya Terhadap Tingkat Kesejahteraan Masyarakat di Kecamatan Kemasrindo, Kertapati Kota Palembang - Yustin Patria Primordia; Nita Astasy; Syeilla Nadira Ikhwan; Dinda Alya Shafira; Suci Orian Sari; Ani Firda Firda (FORUM MEKANIKA, 2023)
The purpose of this study is to be able to find out how the implementation of the BSPS Program affects the handling of RTLH and Extreme Poverty in Kemas Rindo Village, Kertapati District, Palembang City. The data used is secondary data from BKKBN. The data is RTLH data in Palembang City precisely during 2022. Furthermore, the data is analyzed using quantitative descriptive analysis which will later show the distribution of RTLH in the city of Palembang. Other supporting data was obtained based on the Documentation of Kemas Rindo Village Based on the Type and Number of Livelihoods of residents in the Kemas Rindo Village environment, Kertapati District, Palembang City. The results of the discussion that have been presented are related to how the implementation stages of the BSPS Program in Kemas Rindo Village have run well, as evidenced by the development of 53 Habitable Self-Help Housing Units. Then, related to infrastructure, a 917-meter environmental road has also been made for community travel access in Kemas Rindo Village. The completion of RTLH and Extreme Poverty is a manifestation of the Government's concern in alleviating poverty for MBR and it is hoped that this assistance can be felt by all people in need